(untitled) (Research, Society and Development, 2022)
The study aimed to describe the effects of hydrotherapy on balance in aging. This is an integrative review, which is outlined through articles published in academic texts in electronic libraries such as VHL, Scielo and Science Direct. Articles published in English and Portuguese were included by crossing the following descriptors “elderly”, “physiotherapy”, “postural balance” and “hydrotherapy” and their respective terms in English “Elderly”, “physiotherapy”, “postural balance” and “hydrotherapy”. Thus, 16 articles were selected, in Portuguese and English, published between 2008 and 2018. It was found that in the studies, the most used hydrotherapy programs were adaptation to the aquatic environment, heating, stretching, strengthening, active exercises and balance training with eyes open and closed, indicating in their outcomes that the hydrotherapy programs brought satisfactory effects on the balance of the elderly and on the gait, muscle strength and reduction of the risk of falls. Thus, it is essential that this resource is increasingly improved, and properly used in the elderly population, due to its potential positive impact, in helping to maintain the functional capacity of the elderly.